2018
DOI: 10.19080/jdvs.2018.08.555729
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance and Wastage in Large Ruminant (Cattle) in Ethiopia-Review

Abstract: The objective of this paper is to review the reproductive performance and wastage in large ruminants (cow) in Ethiopia. Though the number of female cattle in Ethiopia is high (55.38% (32.0 million)), the production and reproductive performance (crucial factor) needs to be improved. For modern dairy industry, reproductive performance is the most important to determine the efficiency of dairy cattle. Even though, age at first service, age at first calving, day's open, calving interval and number of services per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…The reported average numbers of services per conception (NSC) of the study area were slightly similar with those of Adebabay (2009) that the number of service preconception cross bred cow in bure town was 3.91. The present result is greater than those of Tadesse and Tegegne (2018) and the number of services per conception reported around Mekelle, Bako research center; the overall least squares means in the Maksegnit town and Fogera cows were 2.1±0.1, 1.34±0.11 2.0±0.65 and 1.42±0.05, respectively. According to Mukassa-Mugerwa (1989), cows with values of NSC greater than two, are regarded as poor, the average natural service conception has 1.18 whereas artificial insemination users has 1.5 up to 2.3.…”
Section: Discussioncontrasting
confidence: 76%
“…The reported average numbers of services per conception (NSC) of the study area were slightly similar with those of Adebabay (2009) that the number of service preconception cross bred cow in bure town was 3.91. The present result is greater than those of Tadesse and Tegegne (2018) and the number of services per conception reported around Mekelle, Bako research center; the overall least squares means in the Maksegnit town and Fogera cows were 2.1±0.1, 1.34±0.11 2.0±0.65 and 1.42±0.05, respectively. According to Mukassa-Mugerwa (1989), cows with values of NSC greater than two, are regarded as poor, the average natural service conception has 1.18 whereas artificial insemination users has 1.5 up to 2.3.…”
Section: Discussioncontrasting
confidence: 76%
“…Interval Traits 3.1.1. Age at First Calving (AFC) AFC is the age at which heifers first calve and is also known as the start of the heifer's productive life [23,24]. AFC influences the lifetime production, reproduction of the female, milk production, and lifetime calf crop [25].…”
Section: Reproductive Traits In Dairy Cattlementioning
confidence: 99%
“…Indirectly, AFC affects the cost invested for rearing cattle. The recommended age for the first calving in local breeds is three years, with many experts recommending between 23 and 25 months, which is regarded as optimal for increasing the dairy company's profitability [24]. Previous studies on Thai-Holstein crossbred cattle reported an average AFC value of 32.39 ± 5.76 and 30.97 ± 6.65 months [26,27], higher than the recommended age.…”
Section: Reproductive Traits In Dairy Cattlementioning
confidence: 99%
See 2 more Smart Citations